(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Bioactivities of the methanolic crude extract of root of Bombax ceiba L. and its organic and aqueous soluble partitionates were studied to investigate its medicinal importance. In Free radical scavenging assay by DPPH method, the aqueous soluble partitionate (AQSF) demonstrated the highest free radical scavenging activity with IC50 value of 3.33 ± 0.25 μg/ml. The brine shrimp lethality bioassay of different partitionates of the root demonstrated the significant lethality by the hexane soluble partitionate (HSF) having LC50 value of 1.19 ± 0.10 µg/ml. Among different fractionates of the root, the highest percentage (44.55 ± 0.12%) of clot lysis was exhibited by AQSF. The crude extract revealed promising antidiarrheal, hypoglycemic, central and peripheral analgesic activities at both doses of 200- and 400- mg/kg body weight in Swiss-Albino rat model. Bangladesh Pharmaceutical Journal 22(2): 219-223, 2019